Ecotoxicity assessment in aquaculture system using the test organism Pseudokirchneriella subcapitata (Chlorophyceae) - doi: 10.4025/actascibiolsci.v34i4.9391 (Acta Scientiarum. Biological Sciences, 2012)
The purpose of this study is to perform toxicity tests with microalgae Pseudokirchneriella subcapitata (Chlorophyceae) using inland water samples to evaluate the impact caused by aquaculture. Six field samples were collected ranged November 2006 to March 2007, at Experimental Station, Pindamonhangaba, State of São Paulo. Abiotic factors pointed out to the mesotrophic and eutrophic characteristics already observed at the fish pond and its effluent. The results of ecotoxicological tests carried out with the microalgae Pseudokirchneriella subcapitata showed that the fish pond effluent was potential enough to stimulate the algal growth, therefore eutrophication, to the extent that it is naturally diluted to at least 12.5% of its initial concentration. This type of test can be a tool to be used by environmental managers in attempts to measure the extents of the impacts of effluent discharges from fish farming and to propose treatments based on qualitative and quantitative information.